Legal regulation of the budget process under the conditions of marital state - K. O. Tokarieva (Law and Safety)
The presented publication analyzes the budget process under the conditions of martial law in Ukraine and its legal support. It is argued that the budget process in modern conditions is characterized by such features as: systematicity, cyclicality, legal character, stagedness. Budget process as a set of systematic, consistent and interdependent actions is implemented by relevant entities. In particular, we are talking about the participants in the budget process, the list of which is fixed in the prescriptions of the budget legislation (part 3 of article 19 of the BC of Ukraine). It is noted that such a list is not complete and does not take into account all participants in the budget process, especially those whose activities are related to the limited management of budget funds.